(3GdehghHhf Phh GdJMUjd GdYdej GdeJOfj (B/s - (3SdeGf , SjO UdGM Ydhj s ((3YeGf (B[(3GdCQOf(B] :s (3OHj (B[(3GdEeGQGJ GdYQHjI GdeJMOI(B] :s (3eQcR OjHhfh dJYdje GdJacjQ,s, 2017)
(3jJMOK GdcJGH Yf Cfg jYO GdehghHhf GdKQhI GdMbjbjI dCj eLJeY jQjO dfaSg Cf jhGcH GdeLJeYGJ GdeJbOeI hPdc deG dgPg GdaFI ef OhQ HGQR heJejR aj OYe eSjQI GdJfejI HeaghegG GdhGSY MjK Cf gPg GdaFI HeG JeJdcg ef WGbGJ hbOQGJ hEecGfGJ hehGgH JDgdgG dQSe edGeM GdMGVQ hUjGZI SjfGQjhgGJ GdeSJbHd ef NdGd JhXja bOQGJge GdEHOGYjI aj Md GdeTcdGJ GdhGbYjI GdJj jYGfj efgG GdeLJeY hYdi VhA Pdc jbOe gPG GdcJGH OQGSI HYfhGf GdehghHhf Phh GdJMUjd GdYdej GdeJOfj(B.s
(3HHjdhLQGajI (B: (3UaMI (B183-207.s
Keywords: (3GdWdGH GdehghHhfs -- (3JYdjes; (3GdJMUjd GdYdejs -- (3Jbjjes; (3GdehghHhfs -- (3QYGjIs